Entre a second chance to hopeless circumstance : a social enterprise - Bionat, Natasha Mae; Gonzaga, Shaira Kay; Gonzaga, Shaira kay; Guycoa, Reanne Joy; Jardeleza, Trixia Lois; Libo-on, Nhorie Rose; Malate, Carmina Aileen; Monotilla, Christie Mae
Executive summary-Entre is a company that focuses on creating projects that redefines norms by capitalizing on the untapped reservoir of potentials but hindered by the prejudiced notions thrown upon them. Entre is a company that is imbued with passion to transform lives by making use of the power of entrepreneurial actions and initiatives. The first project ventured by Entre is Project Preso to Negosyo which aims to unleash the stagnant potentials of the Persons Deprived of Liberty (PDL) as well as empower them to once again become an essential part in community building. It also heeds the call to answer the rampant malnutrition cases among school children with 27.4% incidence rate of malnourishment as of 2014 in the province of Iloilo (Panay News, 2014). The realization of this project will be made possible through the Sweet Chains' product line where the company and PDL of Iloilo District Jail-Male Dormitory with Special Intensive Care Area (IDJ-MD with SICA) located in Brgy. Nanga, Pototan, Iloilo are in collaborative efforts together with the different elementary schools on the whole business process. The project will make use of the business model presented below. Identify Target Audience. Entre identified the PDL of IDJ-MD with SICA as its primary target audience for their first ever project-Project Preso to Negosyo because of their great potential as individuals, enthusiasm to improve their lives and the stigma as prisoners attached to them. Needs Assessment. The team assessed the social, human, natural, financial and physical assets of the PDL and IDJ-MD with SICA. This enabled the company to identify the concerns that need to be addressed and the extent of the company's intervention. Innovative Business Model. Through the needs assessment, the company was able to deduce an innovative business model that will be applied in the production, distribution and marketing of the Sweet Chains' product line. The Project Preso to Negosyo starts with the training of the PDL involved in the areas of farming, baking and packaging. This will followed by the production process which will begin with the procurement next, the production and lastly the distribution. The products produced by the PDL are cookies infused with healthy vegetables namely, ampalaya, malunggay and saluyot. The distribution will be done on a bi-weekly schedule to the different elementary schools. Strategic Approach. Entre will have a start-up cost of approximately Php 90,000. The project will undergo three phases namely, pre-launching, launching and retention. To realize the expansion, the goals are realistically divided into three, short-term, mid-term and long-term. The first year of operation will earn a revenue of Php 1,050,000. The preceding years will have an increase in the revenue to Php 1,530,000 in its second year and Php 1,818,000 in its third year. This is because of the increase in the number of partner schools and introduction of the product to the local mini marts and convenience stores as a consignment. Outputs and Outcomes. The project will create an impact not only to the PDL of IDJ-MD with SICA but also to the school children who are susceptible to malnutrition. The actualization of this project will help the PDL to become empowered to once again become part of the society as an agent of nation building. Furthermore, the school children will be able to attend their classes more efficiently that will also contribute later on to the social and economic development of our country. all of these undertakings of the project conform to the Sustainable Development Goals set by the United Nations. This innovative and socially inclined business will surely create a sound and responsible business environment that would serve as a beacon to those who need the aid of entrepreneurial action. PROJECTS HIGHLIGHTS: 1. Sustainable business venture and community a) 1 company ; b) 1 project ; c) 7 members ; d)240,226 income ; e) 15 direct impact ; f) 1800 indirect impact.